2017
DOI: 10.1017/s0007114517001398
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal vitamin D status in pregnancy and neurodevelopmental outcomes in childhood: results from the Avon Longitudinal Study of Parents and Children (ALSPAC)

Abstract: Seafood intake in pregnancy has been positively associated with childhood cognitive outcomes which could potentially relate to the high vitamin D content of oily fish. However, whether higher maternal vitamin D status (serum 25-hydroxyvitamin D (25(OH)D)) in pregnancy is associated with a reduced risk of offspring suboptimal neurodevelopmental outcomes is unclear. A total of 7065 mother-child pairs were studied from the Avon Longitudinal Study of Parents and Children cohort who had data for both serum total 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
2
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 39 publications
6
48
2
1
Order By: Relevance
“…Therefore, any peak in November in mean fetal lateral cerebral ventricle size is likely to relate to an exposure occurring in the preceding summer and/or autumn. Maternal vitamin D status is at its highest during summer and autumn in the United Kingdom: our data do not therefore support a protective role for higher 25(OH)D levels against fetal lateral cerebral ventriculomegaly. Alternative explanations for our findings should therefore be considered.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Therefore, any peak in November in mean fetal lateral cerebral ventricle size is likely to relate to an exposure occurring in the preceding summer and/or autumn. Maternal vitamin D status is at its highest during summer and autumn in the United Kingdom: our data do not therefore support a protective role for higher 25(OH)D levels against fetal lateral cerebral ventriculomegaly. Alternative explanations for our findings should therefore be considered.…”
Section: Discussioncontrasting
confidence: 92%
“…The mechanisms by which this effect is mediated are uncertain, but studies in rats show that developmental vitamin D deficiency is associated with impaired cellular differentiation across a number of brain regions and altered brain expression of genes involved in cytoskeleton maintenance and neurotransmission . Circulating concentrations of 25‐hydroxyvitamin D (25[OH]D, the measure of vitamin D status) exhibit seasonality among pregnant women in the United Kingdom, with peak levels in early autumn and trough levels in spring reflecting variation in exposure to ultraviolet B radiation in sunshine which stimulates cutaneous vitamin D synthesis . We reasoned that, if vitamin D status does influence neurodevelopment, this might be reflected by seasonal variation in lateral cerebral ventricular diameter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies did not find any association between prenatal vitamin D levels and global IQ or cognitive development at preschool [69][70][71][72] and school age [73,74]. However, Keim et al [75] reported a positive association between both maternal and cord blood 25(OH)D concentration and IQ at age 7, but the effect estimates were very small.…”
Section: Global Intelligence Quotient (Iq) or Cognitive Developmentmentioning
confidence: 99%
“…Two studies reported increased psychomotor scores at age 14 months [51] and at 30 months [74] associated with higher maternal vitamin D concentrations in pregnancy. However, 4 studies did not find any association [69,71,72,75].…”
Section: Psychomotor Outcomesmentioning
confidence: 99%